Survodutide - Novel Anti Obesity Drug - Irtiqa Ayani Rathore; Sana Malik; Amarjeet Singh; Vishal R Tandon; Annil Mahajan (JK Science)
Survodutide (BI 456906) is a novel, dual agonist of glucagon and glucagon-like peptide-1 (GLP-1) receptors developed as a once-weekly subcutaneous injection for the management of obesity. While GLP-1 receptor agonists have shown promise in managing obesity and associated complications, survodutide combines GLP-1 and glucagon receptor agonism to potentially enhance weight loss and address obesity-related co-morbidities.